Impact of cage culture in reservoir on the livelihood of fishers: A case study in Jharkhand, India - Pandit, Arun; Das, B. K.; Chandra, Ganesh; Roy, Aparna; Debroy, Piyashi; Yadav, A. K.; Chakraborty, L.; Biswas, D. K. (Indian Journal of Fisheries, 2021)
Cage fish farming in Indian reservoirs has the potential to enhance the reservoir production manifold. The present study estimated that around 14,000 cages have been installed in different reservoirs of the country which are producing around 16% of the current reservoir fish production. Around 7.5 lakh mandays of labour are being generated by cage fish farming in the country. An empirical study in the state of Jharkhand State found that  the adoption of cage culture contributed around 30%  to the  livelihood of fishers. Cage culture not only increased monthly family income but also reduced the occupational migration. The fishermen households who adopted cage farming also accumulated some durable assets due to improvement in household income. However, high initial cost of cage culture operation, high feed cost and low market price of cultured pangas fish (Pangasianodon hypophthalmus) were some of the major constraints in adopting the technology as reported by the fishers. The study recommends that the state departments need to promote  the use of low cost galvanised iron(GI) cages designed by the ICAR-Central Inland Fisheries Research Institute (ICAR-CIFRI) in reservoirs  which may play a significant role in fulfilling the vision of blue revolution in the country.Keywords: Cage fish farming, Livelihood, Pangasianodon hypophthalmus, Reservoir